Phenotypic and imaging spectrum associated wth WDR45 - Adang, Laura A.; Pizzino, Amy; Malhotra, Alka; Dubbs, Holly; Williams, Catherine; Sherbini, Omar; Anttonen, Anna-Kaisa; Lesca, Gaetan; Linnankivi, Tarja; Laurencin, Chloé; Milh, Matthieu; Perrine, Charles; et al. (Pediatric neurology, 2020)
Background - Mutations in the X-linked gene WDR45 cause neurodegeneration with brain iron accumulation type 5. Global developmental delay occurs at an early age with slow progression to dystonia, parkinsonism, and dementia due to progressive iron accumulation in the brain. - Methods - We present 17 new cases and reviewed 106 reported cases of neurodegeneration with brain iron accumulation type 5. Detailed information related to developmental history and key time to event measures was collected. - Results - Within this cohort, there were 19 males. Most individuals were molecularly diagnosed by whole-exome testing. Overall 10 novel variants were identified across 11 subjects. All individuals were affected by developmental delay, most prominently in verbal skills. Most individuals experienced a decline in motor and cognitive skills. Although most individuals were affected by seizures, the spectrum ranged from provoked seizures to intractable epilepsy. The imaging findings varied as well, often evolving over time. The classic iron accumulation in the globus pallidus and substantia nigra was noted in half of our cohort and was associated with older age of image acquisition, whereas myelination abnormalities were associated with younger age. - Conclusions - WDR45 mutations lead to a progressive and evolving disorder whose diagnosis is often delayed. Developmental delay and seizures predominate in early childhood, followed by a progressive decline of neurological function. There is variable expressivity in the clinical phenotypes of individuals with WDR45 mutations, suggesting that this gene should be considered in the diagnostic evaluation of children with myelination abnormalities, iron deposition, developmental delay, and epilepsy depending on the age at evaluation.